Musings post colonies - Akhter, Maswood (Rajshahi, Bangladesh : Chinno, 2012)
Contributed articles.
Includes bibliographical references.
AAL
Keywords: Postcolonialism in literature; Postcolonialism -- Commonwealth countries; Colonies in literature -- History